Designing a Transparent CdIn2S4/In2S3 Bulk‐Heterojunction Photoanode Integrated with a Perovskite Solar Cell for Unbiased Water Splitting. Issue 30 (22nd June 2020) - Meng, Linxing; Wang, Min; Sun, Haoxuan; Tian, Wei; Xiao, Chenhong; Wu, Shaolong; Cao, Fengren; Li, Liang
Abstract: The integration of photoelectrochemical photoanodes and solar cells to build an unbiased solar‐to‐hydrogen (STH) conversion system provides a promising way to solve the energy crisis. The key point is to develop highly transparent photoanodes, while its bulk separation efficiency (ηsep. ) and surface injection efficiency are as high as possible. To resolve this contradiction, first a novel CdIn2 S4 /In2 S3 bulk heterojunctions in the interior of nanosheets is designed as a photoanode with high transparency and an ultrahigh ηsep. up to 90%. Furthermore, decorating the ultrathin amorphous SnO2 layer by atomic layer deposition, the surface oxygen‐evolution kinetics of the photoanode are increased significantly. As a result, the onset potential of the photoanode shifts negatively to 0.02 V vs RHE, and the photocurrent density boosts to 2.98 mA cm −2 at 1.23 V vs RHE, which is ten times higher than that of pristine CdIn2 S4 . Such a high‐performance photoanode enables the integrated metal sulfide photoanode–perovskite solar cell system to deliver a STH conversion efficiency of 3.3%. Abstract : CdIn2 S4 /In2 S3 bulk heterojunction nanosheet arrays are designed as photoanodes of photoelectrochemical cells, which have high transparency and high separation efficiency up to 90%. This photoanode is integrated with a perovskite solar cell to form an unbiased solar water‐splitting system, delivering a solar to hydrogen conversion efficiency of 3.3%.